Correlating structure with mechanical properties in lithium borophosphate glasses. (17th June 2022) - Liu, Pengfei; Youngman, Randall E.; Jensen, Lars R.; Smedskjaer, Morten M.
Abstract: Connecting structure with mechanical properties is needed for improving the mechanical reliability of oxide glasses. Although the mechanical properties of silicate and borosilicate glasses have been intensively studied, this is not the case for phosphate and borophosphate glasses. To this end, we here study the structure, density, glass transition, hardness, elasticity, and cracking behavior of lithium borophosphate glasses. The glasses are designed with different B/P ratios to access different boron and phosphorus speciation. The introduction of boron in the phosphate network increases the average network rigidity because of the reduction in the fraction of nonbridging oxygens as well as the exchange of phosphate groups with more constrained BO4 groups. These structural changes result in an increase in density, Vickers hardness, glass transition temperature, and Young's modulus, and a decrease in Poisson's ratio for higher B2 O3 content. Furthermore, the increase in network rigidity and atomic packing density results in a lower ability of the glasses to densify upon indentation, resulting in an overall decrease in crack initiation resistance. Finally, we find an increase in the fraction of trigonal boron units in the high‐B2 O3 glasses, which has a significant effect on atomic packing density and Vickers hardness.